Priority Competencies Of Managers In The Modern Dynamic Organisational Environment - Miroslaw BETKOWSKI (Communications of International Proceedings, 2023)
The author of this article discusses the significance of managerial competencies in modern organizations. The article highlights the dynamic nature of changes in the present-day business environment, which necessitates appropriate managerial skills, knowledge, experience, and personal traits. Managerial competencies encompass a range of organizational activities, including the provision of high-quality products or services. Additionally, these competencies are essential for managers as they directly influence their employees and their performance. The development of managerial competencies is crucial in contemporary organizations to tackle challenges and potential failures that may arise while fulfilling organizational tasks. Managers must continuously enhance their skills to effectively lead their teams and achieve goals. The article presents a set of managerial competencies in modern organizations, derived from research conducted in selected companies. The objective of the research was to identify the most influential competencies that contribute to organizational effectiveness and success. The findings indicate that key managerial competencies include team management, decision-making skills, interpersonal communication, and the ability to adapt to ever-changing business conditions. Leadership skills, employee motivation, and fostering a positive atmosphere also play significant roles. In conclusion, the article provides recommendations for managers who aspire to develop their competencies and effectively manage modern organizations. The author underscores the vital role of competencies in achieving success and emphasizes the necessity for continuous development and improvement among managers.
Keywords: Manager; Competencies; Competency Model; Preferred Competencies